(untitled) (Dissertare, 2017)
The purpose of this essay is to generate reflexive processes inherent to ontological coaching as a managerial approach, in order to enhance the personal and professional development of those who make life in companies. Assuming a hermeneutical position, through a dialectic process with the texts and the own experience, it is understood the ontological coaching, on the basis of the ontology of the language and from the consideration that the organizations learn from the learning of the individuals that the compose For what is required, a new understanding, with managers oriented to glimpse their responsibility for the lives of so many people in their charge, where knowledge is generated in the way of conversations that will take place between the coachee and his coach, who counts with competencies: listening, speaking and observing, which make it easier for individuals and teams to take care of their own concerns and to break the barriers that limit change and transformation, in order to achieve goals that seemed unattainable and achieve organizational development, through a management that is based on knowledge management and a certain ethics of coexistence.